Implementasi edugame mobile untuk pembelajaran anggah ungguhin basa Bali di SD negeri 5 Mengwitani, Badung Bali - I ketut Setiawan; Putu Candra Kharisma Dewi (Asosiasi Program Studi Desain Komunikasi Visual Indonesia (Asprodi DKV), 2025)
The decline in students’ interest and understanding of Anggah Ungguhin Basa Bali presents a significant challenge in Balinese language learning at the elementary level. This study aims to design and implement an interactive mobile-based edugame to enhance the comprehension of fifth-grade students at SD Negeri 5 Mengwitani. The research employed a research and development (R&D) method using both qualitative and quantitative approaches. Data were collected through observation, interviews, documentation, and pre-test and post-test assessments. The results indicate a substantial improvement in students’ average scores, increasing from 40.9 in the pre-test to 91.3 in the post-test. Expert evaluations from media, content, and user perspectives also rated the edugame in the “highly feasible” category, with percentages above 90%. These findings demonstrate that mobile-based edugames are not only effective in improving learning outcomes but also play a vital role in preserving the Balinese language. The applied visual communication design successfully created a contextual, engaging, and student-friendly learning experience, making the edugame an innovative solution for teaching local content in elementary schools.